2014
DOI: 10.1136/jramc-2013-000178
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Shock Index as a secondary triage tool

Abstract: RCDM/Res/Audit/1036/12/0050.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…Its predicting value for the outcome has been fully demonstrated in the patients with trauma [1][2][3][4]. Recently, some studies further showed that a new index, MSI, in the ED is a more valuable marker for predicting the mortality rate than SI alone in adult patients with trauma [14].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Its predicting value for the outcome has been fully demonstrated in the patients with trauma [1][2][3][4]. Recently, some studies further showed that a new index, MSI, in the ED is a more valuable marker for predicting the mortality rate than SI alone in adult patients with trauma [14].…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated as a useful predictor for hospital mortality among adult patients with trauma [1][2][3]. Shock index is better not only than SBP, diastolic blood pressure (DBP), and HR alone but also than some risk stratification systems, for example, SI is more useful than the Triage Sort (TSO) for secondary triage in a mass-casualty situation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical assessment and standard coagulation assays are still the most commonly used tools in this context according to the literature [15,16] and, therefore, still play a major role in level I trauma centres as shown here. The Shock Index (SI) defined by the ratio of heart rate to systolic blood pressure has recently been advocated as a clinical indicator of hypovolaemic shock in respect to transfusion requirement, haemostatic resuscitation and outcome [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Once within the casualty clearing station or other permissive environment, secondary triage can occur, allowing for refinement of the triage process and a reduction in patients overtriaged. The Triage Sort as it exists currently shows limited performance for predicting the need for life-saving intervention19; we speculate that future work may be required in order to refine the Triage Sort, and support the consideration of including an assessment of anatomical injury, mechanism of injury and clinical acumen.…”
Section: Discussionmentioning
confidence: 93%